Optimal Tikhonov approximation for a sideways parabolic equation - Chu-Li Fu; Hong-Fang Li; Xiang-Tuan Xiong; Peng Fu (International Journal of Mathematics and Mathematical Sciences)
We consider an inverse heat conduction problem with convection term which appears in some applied subjects. This problem is ill posed in the sense that the solution (if it exists) does not depend continuously on the data. A generalized Tikhonov regularization method for this problem is given, which realizes the best possible accuracy.